Analisis Kinerja KeuanganProyek Pembangunan Sentral PLTD Unit VII Gudang Garam Kediri Menggunakan Metode Earned Value (Eva) - Maghfiroh, Syntya Arum Dani; Mega Hastuti, Sri Wahyuni (Universitas Islam Kadiri, 2024)
A project is a temporary series of activities that takes place within a limited timeframe, with allocated specific resources, and is intended to carry out tasks whose objectives have been clearly defined. In a project, project management is necessary to organize, coordinate, and carry out activities within the project, such as the development project of the PLTD Unit VII Warehouse of Gudang Garam Kediri, which is the subject of this research. Project control is needed to ensure that the project is completed according to plan. Value analysis can be applied to determine the performance index of completed project work. The performance of the project execution in the 20th week in terms of cost shows that project expenses are higher than planned costs, as indicated by the Cost Performance Index (CPI) with a result of 0.898 < 1. Meanwhile, in terms of schedule, there is a delay, indicated by the Schedule Performance Index (SPI) with a result of 0.960 < 1. If the project execution performance in the 20th week remains the same until the end of the project, the estimated total cost of project execution (EAC) required is Rp. 36,421,987,702.67, then the project will incur a loss of Rp. 3,710,669,761.04 or a loss percentage of 11.334% from the planned cost. The estimated project completion time (EAS) based on reporting data in the 20th week is 52.66 weeks, indicating a delay in completing the work of 16.66 weeks or a delay percentage of 46.28% from the planned project schedule of 36 weeks. Some solutions to overcome the occurring delay include adding overtime work hours to critical path activities, implementing shift work systems, and maximizing the productivity of labor and available tools.